Prediction on localized necking in sheet metal forming : finite element simulation and plastic instability in complex industrial strain paths - A. Barata da Rocha (2007)
The use of Finite Element Simulation allows accurate predictions of stress and strain distributions in complex stamped parts. The onset of necking is strongly dependent on the strain paths imposed to the parts and therefore the prediction of localized necking can be a difficult task. Numerical models of plastic instability have been used to predict such behavior and recent and more accurate constitutive models have been applied in these calculations. In many manufacturing areas such as automotive, aerospace, building, packaging and electronic industries, the optimization of sheet metal processes, through the use of numerical simulations, has become a key factor to a continuously increasing requirement for time and cost efficiency, for quality improvement and materials saving. This paper makes an analysis of the evolution of strain gradients in stamped parts. The combination of Finite Element Analysis with a Plastic Instability Model, developed to predict localized necking under complex strain paths, shows that it is possible to predict failure with precision. Several constitutive laws are used and comparisons are made with experiments in stamped benchmark parts. Considering non linear strain paths, as detected in stamped parts, more accurate failure predictions are achieved. The work described in this paper shows the need to include a post processor analysis of failure, capable of predicting the behavior of the material under non linear strain paths. Taking this phenomenon into account, it is shown that it is possible to increase the accuracy of the onset of localized necking prediction.